The book of the thousand nights and a night : a plain and literal translation of the Arabian nights entertainments. Volume eight - Burton, Richard Francis, Sir, 1821-1890; Leighton, Frederick; Burton Club (London: Privately printed by the Burton Club, 1885)
The Book of the Thousand Nights and a Night (1885), is a celebrated English language translation of One Thousand and One Nights (the "Arabian Nights") - a collection of Middle Eastern and South Asian stories and folk tales compiled in Arabic during the Islamic Golden Age (8th−13th centuries) - by the British explorer and Arabist Richard Francis Burton (1821-1890)
v. 8. The book of the thousand nights and a night
Estimated date of publication from Penzer.
Printed in the United States of America.
Includes bibliographical references and indexes.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Fairy tales; Tales, Arabic; Folklore -- Arabian Peninsula; Arabian Peninsula -- Folklore